South Polar chart / from various authorities with amendments and additions to 1912 (Great Britain. Hydrographic Office, 1920)
New edition . 9th Octr. 1914. Small corrections . 1920 Relief shown by spot heights and hachures. Depths shown by soundings.; Includes "Explanation of the sledge tracks" showing 4 explorere routes. Color;